Targeted Self-Emulsifying Drug Delivery Systems to Restore Docetaxel Sensitivity in Resistant Tumors - Virginia Campani; Iris Chiara Salaroglio; Valeria Nele; Joanna Kopecka; Andreas Bernkop-Schnürch; Chiara Riganti; Giuseppe De Rosa (MDPI AG, 2022)
The use of chemotherapeutic agents such as docetaxel (DTX) in anticancer therapy is often correlated to side effects and the occurrence of drug resistance, which substantially impair the efficacy of the drug. Here, we demonstrate that self-emulsifying drug delivery systems (SEDDS) coated with enoxaparin (Enox) are a promising strategy to deliver DTX in resistant tumors. DTX partition studies between the SEDDS pre-concentrate and the release medium (water) suggest that the drug is well retained within the SEDDS upon dilution in the release medium. All SEDDS formulations show droplets with a mean diameter between 110 and 145 nm following dilution in saline and negligible hemolytic activity; the droplet size remains unchanged upon sterilization. Enox-coated SEDDS containing DTX exhibit an enhanced inhibition of cell growth compared to the control on cells of different solid tumors characterized by high levels of FGFR, which is due to an increased DTX internalization mediated by Enox. Moreover, only Enox-coated SEDDS are able to restore the sensitivity to DTX in resistant cells expressing MRP1 and BCRP by inhibiting the activity of these two main efflux transporters for DTX. The efficacy and safety of these formulations is also confirmed in vivo in resistant non-small cell lung cancer xenografts.